Optimal investment with time-varying transition probabilities for regime switching - Hyo-Chan Lee; Seyoung Park; Jong Mun Yoon (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2021)
This study aims to generalize the following result of McDonald and Siegel (1986) on optimal investment: it is optimal for an investor to invest when project cash flows exceed a certain threshold. This study presents other results that refine or extend this one by integrating timing flexibility and changes in cash flows with time-varying transition probabilities for regime switching. This study emphasizes that optimal thresholds are either overvalued or undervalued in the absence of time-varying transition probabilities. Accordingly, the stochastic nature of transition probabilities has important implications to the search for optimal timing of investment.
Keywords: 330; Optimal investment; Time-varying transition probabilities; Regime switching; Cash flows; Option